Peranan Muhammad Iqbal Dalam Rekonstruksi Pemikiran Islam - Tasnim Abdul Rahman, Ahmad Nabil Amir (Al-Makrifat: jurnal kajian Islam, 2024)
Since the middle of 19th century, Muslims have made their ways to variously response to the ideas of modernity, many of which were markedly inspired by the pan-Islamist activist, Jamal al-Din al-Afghani, who started to espouse modern aspiration and inaugurate the Islamic reform movement throughout the Muslim world. This paper highlights the role of Muhammad Iqbal (1879-1938) in Islamic thought, through his philosophical premises to awaken the new Islamic consciousness in the Indian subcontinent, in continuing the tradition of al-Afghani and his religious struggle. The study was qualitative in nature designed based on documentary survey and analysis. It reviews related materials from normative and inductive perspectives. The data were analysed using scientific, descriptive, analytical and historical approaches to reach the final conclusion. The finding shows that Iqbal had formulated unprecedented ideas toward reconstruction and modernization in political, economic and social aspect. His works manifested broad and cohesive philosophical arguments and influences that largely impacted Muslim thought which help to develop their rational and dynamic framework to reconstruct the significance dimension of ijtihad and renewed their profound spiritual and metaphysical consciousness of the perennial and transcendental values of religion and its relevance to the modern context. Keywords: Muhammad Iqbal, religious thought, modernity, metaphysics, ijtihad